IMPLEMENTASI MANAJEMEN BAKAT SEBAGAI SUMBER KEUNGGULAN KOMPETITIF PERUSAHAAN - Suryono Efendi (GoAcademica Research dan Publishing, 2021)
Organizations confront problems in personnel management in this dynamic and competitive business environment. For businesses functioning at a global level, personnel management has become increasingly crucial. The demand for key roles for skilled staff is strong since the organization is to direct them and to lead the organization to the highest level of success. This is why the organization strives for the best staff. The fundamental aim of any corporate strategy is to make the activities that can lead to success more effective and efficiently. When the business builds an excellent team that is comprised of competent staff, talent management is highly crucial.